Suppose that the lucas numbers are $l_n=l_{n-1}+l_{n-2}$ for all $n \ge 1$ where $l_0=2$ and $l_1=1$.

Prove that $l_0^2+l_1^2+...+l_n^2=l_n*l_{n+1}+2$ for $n \ge 0$

I think the easiest way to prove this would be induction. For the base case when $n=0$, we get that $l_0^2=2^2=4=2+2=(2*1)+2=l_0*l_1+2$.

I've tried my hand at proving the inductive step but can't solve it.


We have: $$L_0=2,L_1=1$$ $$L_n=L_{n-1}+L_{n-2}$$ We must prove: $$\sum_{k=0}^{n}L_k^2=L_n\cdot L_{n+1}+2$$ for $n\geq 0$. First, notice how: $$\sum_{k=0}^{0}L_k^2=L_0^2=4=2\cdot1+2=L_0\cdot L_1+2$$ Assume that: $$\sum_{k=0}^{n-1}L_k^2=L_{n-1}\cdot L_n+2$$ Now: $$\sum_{k=0}^{n}L_k^2=L_n^2+\sum_{k=0}^{n-1}L_k^2=L_n^2+L_{n-1}\cdot L_n+2=L_n(L_n+L_{n-1})+2=L_n\cdot L_{n+1}+2$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.